A Study of the Relationship Between Perceived Class Mobility, Philanthropic Sentiment and Consumer Online Giving Behavior Intention - Li Y; Li Q; Yu B; Mou H; Yang X; Xia D (Psychology Research and Behavior Management, 2023)
Yingji Li,1 Qiang Li,2 Bo Yu,1 Hongyi Mou,3 Xin Yang,3 Dongmei Xia4 1School of Humanities and Management, Yunnan University of Chinese Medicine, Kunming, People’s Republic of China; 2School of Economics and Management, Shanghai Technical Institute of Electronics & Information, Shanghai, People’s Republic of China; 3Faculty of Business & Technology, Stamford International University, Bangkok, Thailand; 4Quality Education Center for College Students, Chongqing Institute of Engineering, Chongqing, People’s Republic of ChinaCorrespondence: Dongmei Xia, Email 00137@cqie.edu.cnPurpose: Although the motives of philanthropy vary from country to country around the world, it is still conducive to building a harmonious society to a certain extent.Methods: It uses partial least squares (PLS) to verify the stability of the model and test the model’s hypotheses to analyze the mechanism of action between perceived class mobility and behavioral intention to give online.Results: It was found that perceived class mobility, philanthropic sentiment, and philanthropic cognition affected online giving intention; perceived class mobility had a significant effect on philanthropic cognition and philanthropic sentiment; philanthropic sentiment and philanthropic cognition mediated the relationship between perceived class mobility and giving behavior intention.Conclusion: The study suggests that nonprofit organizations should stimulate behavioral intentions to give by creating an atmosphere of upward class mobility.Keywords: philanthropy, class mobility, philanthropic perception, giving behavior intention